Diabetic Foot- A New Era of Diagnosis and Prevention - PATRYCJA PABIS; MAREK SKOTARSKI; RADOSLAW SZYDLOWSKI; HANNA PORWOLIK; MAGDALENA BODERA; BARTLOMIEJ CZARNECKI; AGATA PORWOLIK; KAMIL STEFANSKI; DOMINIK RABSTEIN; PIOTR DEMBICKI (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Diabetic foot ulcers (DFU), a common complication of long-term diabetes, significantly reduce quality of life, increase morbidity and mortality, and place a heavy burden on individuals and healthcare systems. It is require a multidisciplinary approach to treatment. Aim: To overview the standards in diabetic foot prevention and care. Methods: We searched for materials for this work in the Pubmed and Google Scholar databases using the keywords: "Diabetic foot", "diabetic wounds", "diabetic neuropathy"and analyzed the selected materials. Results: DFU significantly reduce the quality of life and are a major burden for individuals and healthcare systems. Effective care involves specialists across various fields to address the complex causes and improve outcomes. Conclusion:There are currently many published standards for the care and examination of the feet of patients with diabetes, which are presented in the following review. It is important to remember the cause of the pathophysiology of DFU and effectively treat diabetes, maintaining the patient in normoglycemia, and also examine your feet and actively look for the first signs of diabetic ulcers. Keywords: Diabetic foot, diabetic wounds, neuropathy, vascular disease